2019
DOI: 10.3390/fi11010025
|View full text |Cite
|
Sign up to set email alerts
|

Smart System for Prediction of Accurate Surface Electromyography Signals Using an Artificial Neural Network

Abstract: Bioelectric signals are used to measure electrical potential, but there are different types of signals. The electromyography (EMG) is a type of bioelectric signal used to monitor and recode the electrical activity of the muscles. The current work aims to model and reproduce surface EMG (SEMG) signals using an artificial neural network. Such research can aid studies into life enhancement for those suffering from damage or disease affecting their nervous system. The SEMG signal is collected from the surface abov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…It's not just handy that the good effects happen; they often have big effects [8], [9], [10]. However, the complexity of human language, which includes subtleties in syntax, meaning, and pragmatics, makes it very hard to get very accurate question classification [11], [12]. Support Vector Machines, Random Forests, and other machine learning models have been used for this, but new developments in deep learning and transformer models like BERT, RoBERTa, and ELECTRA have shown that they work even better than expected [13].…”
Section: Introductionmentioning
confidence: 99%
“…It's not just handy that the good effects happen; they often have big effects [8], [9], [10]. However, the complexity of human language, which includes subtleties in syntax, meaning, and pragmatics, makes it very hard to get very accurate question classification [11], [12]. Support Vector Machines, Random Forests, and other machine learning models have been used for this, but new developments in deep learning and transformer models like BERT, RoBERTa, and ELECTRA have shown that they work even better than expected [13].…”
Section: Introductionmentioning
confidence: 99%
“…[ 24 ] Various methods have been proposed to predict EMG signals, and some of the related parameters, namely signal parameters such as biceps force, have been estimated for different loads to predict the angle of the joints. [ 25 26 27 28 ] In some other methods, different parameters belonging to the signal, such as waveform length, root minimum square, slope sign change, zero crossing, and simple square integral, have been applied. [ 29 30 31 32 33 34 35 ] Machine learning algorithm methods, including the support vector machine and random forest,[ 36 ] has been applied to predict muscle activity, none of which has predicted the EMG signal.…”
Section: Introductionmentioning
confidence: 99%
“…For example, some studies tested both TD and FD features as input data [ 19 , 20 ], and others applied raw EMG signals directly to the ANN without a feature extraction process [ 21 , 22 ]. Additionally, the application of research was not limited to hand/finger gesture recognition but included the prediction of force load [ 23 , 24 ] and the detection of neuromuscular disorders [ 25 ]. However, studies that applied ANN algorithms to TD features only, excluding other features or data types, for hand/finger gesture recognition, have not been conducted as extensively as other EMG studies, which used both TD and FD features or raw EMG signals for various purposes [ 26 ].…”
Section: Introductionmentioning
confidence: 99%